Miscantus – energy culture for the production of biofuel - Ястремська, Л. С.; Пришляк, Р. І.; Федонюк, Ю. В. (Problems of Environmental Biotechnology, 2017)
Features of plants of the genus Miscanthus, growth conditions, chemical properties and use of miscanthus as a perspective energy culture in Ukraine for biofuel production are considered. Miscanthus biomass can be used as an ecological substitute for traditional fuels, as well as for the production of ethanol.